Employability skills in vocational high school context: An analysis of the KTSP curriculum - Muhammad Sayuti; Mujiarto Mujiarto (Journal of Vocational Education Studies, 2018)
Employability skills for students are believed to reduce the mismatch between the supply of vocational high school graduates and the demand of job vacancy from industry. For more than three centuries, the gap between the vocational high school and the workplace has become people’s concern. It seems that this issue will not end in the near future, rather will be more interesting to be studied because of the complexity of the relationship between the two sectors. The objective of this study, therefore, is to discover of how well employability skills is adopted in the school level curriculum (KTSP) of vocational high schools in Indonesia. To achieve the research’s objective, the content analysis to the curriculum was applied. The analysis of KTSP in the subject of entrepreneurship (ENT) and the computer and information management (KKPI) discovers the limited concern and the incomprehensive areas of employability skills adopted. The research findings demand the government to improve the content of employability skills in the curriculum, especially in dealing with the high unemployment rate of vocational high school graduates.